Soft magnetic powder, dust core, magnetic element, electronic device and mobile device

JP7632047B2Active Publication Date: 2025-02-19SEIKO EPSON CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021081263
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-12
Publication Date
2025-02-19
Estimated Expiration
2041-05-12

Smart Images

  • Figure 0007632047000003
    Figure 0007632047000003
  • Figure 0007632047000004
    Figure 0007632047000004
  • Figure 0007632047000005
    Figure 0007632047000005
Patent Text Reader

Abstract

To provide soft magnetic powder capable of achieving low coercivity by being subjected to heat treatment, as well as a powder magnetic core, a magnetic element, an electronic device, and a mobile body.SOLUTION: Soft magnetic powder includes amorphous metal particles having a composition formula represented by Fe100-a-b-c-d-e-f-gCraSibBcCdAleTifCog, [wherein a, b, c, d, e, f, and g are numbers representing atomic percentages, satisfying 0<a≤3.0, 5.0≤b≤15.0, 7.0≤c≤15.0, 0.1≤d≤3.0, 0<e≤0.016, 0<f≤0.009, 0≤g≤0.025.]SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to soft magnetic powder, a compacted magnetic core, a magnetic element, an electronic device, and a moving body.

Background Art

[0002] Patent Document 1 discloses an iron-based metallic glass alloy powder represented by the compositional formula (Fe 1-s-t Co s Ni t ) 100-x-y {(Si a B b ) m (P c C d ) n} x M y wherein x, y, s, and t in the compositional formula satisfy 19 ≦ x ≦ 30, 0 < y ≦ 6, 0 ≦ s ≦ 0.35, 0 ≦ t ≦ 0.35, and s + t ≦ 0.35. Further, at least one of Cr or Zr is added as a corrosion resistance modifying component to this iron-based metallic glass alloy powder, and at least one of V, Ti, Ta, Cu, and Mn is added as a corrosion resistance modifying sub-component.

[0003] Since such an iron-based metallic glass alloy powder contains an amorphous single phase, its magnetic properties can be improved. Further, in this iron-based metallic glass alloy powder, since a corrosion resistance modifying component and a corrosion resistance modifying sub-component are added, its corrosion resistance and specific resistance are improved.

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Summary of the Invention

Problems to be Solved by the Invention

[0005] Powder compacts such as dust cores manufactured using soft magnetic powders are often used in the high frequency range. In the high frequency range, the core loss of the powder compacts tends to increase, so suppressing the core loss is an issue. The composition of the soft magnetic powder is likely to contribute to suppressing the hysteresis loss, which is a type of core loss. In order to suppress the hysteresis loss, it is necessary to reduce the coercive force of the soft magnetic powder.

[0006] However, the iron-based metallic glass alloy powder described in Patent Document 1 does not take into consideration the effect of its composition on the coercive force, so there is a need to develop a soft magnetic powder that has good magnetic properties due to the amorphous alloy and also has a low coercive force. [Means for solving the problem]

[0007] The soft magnetic powder according to the application example of the present invention is Composition formula Fe 100-a-b-c-d-e-f-g Cr a S b B c C d Al e Ti f Co g [wherein a, b, c, d, e, f and g are numbers representing atomic percent, 0 <a≦3.0、 5.0≦b≦15.0, 7.0≦c≦15.0, 0.1≦d≦3.0, 0 <e≦0.016、 0 <f≦0.009、 0≦g≦0.025, .] The amorphous metal particles have a composition represented by the formula:

[0008] The powder magnetic core according to the application example of the present invention is The soft magnetic powder according to the application example of the present invention is included.

[0009] The magnetic element according to the application example of the present invention includes: The present invention is characterized by including a powder magnetic core according to an application example of the present invention.

[0010] The electronic device according to the application example of the present invention includes: The present invention is characterized by including a magnetic element according to an application example of the present invention.

[0011] A moving body according to an application example of the present invention is The present invention is characterized by including a magnetic element according to an application example of the present invention. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a plan view illustrating a schematic diagram of a toroidal type coil component. [Diagram 2] FIG. 2 is a see-through perspective view that typically illustrates a closed magnetic circuit type coil component. [Diagram 3] FIG. 1 is a perspective view showing a mobile personal computer, which is an electronic device including a magnetic element according to an embodiment. [Figure 4] FIG. 1 is a plan view showing a smartphone, which is an electronic device including a magnetic element according to an embodiment. [Diagram 5] FIG. 1 is a perspective view showing a digital still camera, which is an electronic device including a magnetic element according to an embodiment. [Figure 6] FIG. 1 is a perspective view showing an automobile, which is a moving body including a magnetic element according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, the soft magnetic powder, the dust core, the magnetic element, the electronic device, and the mobile body of the present invention will be described in detail with reference to preferred embodiments shown in the accompanying drawings.

[0014] 1. Soft magnetic powder The soft magnetic powder according to the embodiment is a metal powder exhibiting soft magnetism. Such soft magnetic powder can be used for any purpose, but for example, the particles are bound together via a binder and used to manufacture various types of compacts such as dust cores and electromagnetic wave absorbing materials.

[0015] 1.1.Composition The soft magnetic powder according to the embodiment has the composition formula Fe 100-a-b-c-d-e-f-g Cr a S b B c C d Al e Ti f Co g The amorphous metal particles have a composition represented by the formula: a, b, c, d, e, f and g are numbers representing atomic percentages. a, b, c, d, e, f and g are 0 <a≦3.0、 5.0≦b≦15.0, 7.0≦c≦15.0, 0.1≦d≦3.0, 0 <e≦0.016、 0 <f≦0.009、 0≦g≦0.025, Meet the following.

[0016] Since such soft magnetic powders contain amorphous metal particles, the magnetic anisotropy is reduced compared to powders containing crystalline metal particles, improving magnetic properties such as magnetic permeability while decreasing coercive force.

[0017] In addition, since the amorphous metal particles have the above composition, the soft magnetic powder becomes a powder that has a further reduced coercive force when heat treated. The heat treatment serves to reduce various defects and anisotropy (stress-induced anisotropy) that are introduced when manufacturing the soft magnetic powder. Therefore, the soft magnetic powder is designed in anticipation of the decrease in coercive force due to heat treatment, but depending on the composition, the decrease is limited.

[0018] In contrast, by including amorphous metal particles having the above-mentioned composition, the soft magnetic powder according to this embodiment can suppress the crystallization of the amorphous metal by heat treatment while sufficiently reducing the coercive force by heat treatment. Therefore, the soft magnetic powder after heat treatment can achieve both high magnetic permeability and low coercive force. By using such soft magnetic powder, it is possible to realize a compact that contributes to the miniaturization and high efficiency of magnetic elements. In this specification, various defects and anisotropy are also referred to as "distortion".

[0019] The soft magnetic powder may contain any soft magnetic powder or non-magnetic powder in addition to the amorphous metal particles having the above-mentioned composition, but the content of amorphous metal particles is preferably 50 mass% or more, more preferably 80 mass% or more, and even more preferably 90 mass% or more.

[0020] The composition of the amorphous metal particles will be described below. Fe (iron) has a significant effect on the basic magnetic properties and mechanical properties of the amorphous metal particles according to the embodiment.

[0021] The Fe content is expressed as 100-abcdefg. However, due to the influence of impurities, deviation of up to ±0.50 atomic % from 100-abcdefg is permitted.

[0022] The Fe content is not particularly limited, but is preferably from 70.0 atomic % to 81.0 atomic % and more preferably from 72.0 atomic % to 75.0 atomic %.

[0023] If the Fe content is below the lower limit, the magnetic permeability and saturation magnetic flux density of the amorphous metal particles may decrease, whereas if the Fe content is above the upper limit, it may become difficult to stably form an amorphous structure during the production of the amorphous metal particles.

[0024] Cr (chromium) acts to improve the corrosion resistance of amorphous metal particles. This is presumably due to the formation of a passive film mainly composed of chromium oxide. By improving the corrosion resistance, the oxidation of amorphous metal particles can be suppressed, and a decrease in magnetic properties associated with oxidation can be inhibited. In addition, the passive film also contributes to increasing the insulation between amorphous metal particles and suppressing the eddy current loss of the compacted powder.

[0025] The content rate a of Cr satisfies 0 < a ≤ 3.0, preferably satisfies 1.1 ≤ a ≤ 2.7, and more preferably satisfies 1.2 ≤ a ≤ 2.5. When the content rate a of Cr is below the lower limit value, the corrosion resistance decreases, and the magnetic properties of the amorphous metal particles may deteriorate over time. On the other hand, when the content rate a of Cr exceeds the upper limit value, the amorphization is inhibited during the production of the amorphous metal particles, so the magnetic anisotropy increases and the magnetic permeability may decrease.

[0026] Si (silicon) promotes amorphization during the production of amorphous metal particles. Thereby, when the soft magnetic powder is heat-treated, the crystallization of the amorphous metal particles is suppressed. In addition, Si also contributes to increasing the magnetic permeability of the amorphous metal particles.

[0027] The content rate b of Si satisfies 5.0 ≤ b ≤ 15.0, preferably satisfies 8.0 ≤ b ≤ 13.5, and more preferably satisfies 10.5 ≤ b ≤ 12.0. When the content rate b of Si is below the lower limit value, the amorphization is inhibited, and the magnetic permeability of the amorphous metal particles may decrease. On the other hand, when the content rate b of Si exceeds the upper limit value, the saturation magnetic flux density may decrease.

[0028] B (boron) promotes amorphization during the production of amorphous metal particles. Thereby, when the soft magnetic powder is heat-treated, the crystallization of the amorphous metal particles is suppressed. In addition, B also contributes to increasing the magnetic permeability of the amorphous metal particles. Furthermore, by using Si and B in combination, amorphization can be synergistically promoted based on the difference in atomic radius between the two.

[0029] The B content c satisfies 7.0≦c≦15.0, preferably 8.0≦c≦13.5, and more preferably 10.5≦c≦12.0. If the B content c is below the lower limit, amorphization may be inhibited and the magnetic permeability of the amorphous metal particles may decrease. On the other hand, if the B content c is above the upper limit, the saturation magnetic flux density may decrease.

[0030] When the raw material for amorphous metal particles is melted, C (carbon) reduces the viscosity of the melt, facilitating amorphization and pulverization. This makes it possible to realize amorphous metal particles with small diameters and high magnetic permeability. As a result, it is possible to suppress not only hysteresis loss but also eddy current loss in the high frequency range.

[0031] The C content d satisfies 0.1≦d≦3.0, preferably 1.3≦d≦2.8, and more preferably 1.7≦d≦2.5. If the C content d is below the lower limit, the viscosity of the melt is not sufficiently reduced, and the amorphous metal particles are likely to have an irregular shape. This may reduce the filling property during compaction, and the saturation magnetic flux density of the compact may not be sufficiently increased. On the other hand, if the C content d is above the upper limit, the amorphousization may be inhibited, and the magnetic permeability of the amorphous metal particles may be reduced.

[0032] The addition of a small amount of aluminum (Al) promotes the reduction of distortion when the amorphous metal particles are heat-treated, and therefore the heat-treated soft magnetic powder can achieve both high magnetic permeability and low coercivity.

[0033] The content ratio e of Al satisfies 0 < e ≤ 0.016, preferably satisfies 0.001 ≤ e ≤ 0.009, and more preferably satisfies 0.003 ≤ e ≤ 0.007. When the content ratio e of Al is lower than the lower limit value, there is a possibility that the coercive force cannot be sufficiently reduced when the amorphous metal particles are heat-treated. On the other hand, when the content ratio e of Al exceeds the upper limit value, the amorphization is inhibited, and there is a possibility that crystallization is likely to occur when the amorphous metal particles are heat-treated.

[0034] When Ti (titanium) is added in a trace amount, it promotes the reduction of strain when the amorphous metal particles are heat-treated. Therefore, in the soft magnetic powder after heat treatment, it is possible to achieve both high magnetic permeability and low coercive force.

[0035] The content ratio f of Ti satisfies 0 < f ≤ 0.009, preferably satisfies 0.001 ≤ f ≤ 0.008, and more preferably satisfies 0.003 ≤ f ≤ 0.007. When the content ratio f of Ti is lower than the lower limit value, there is a possibility that the coercive force cannot be sufficiently reduced when the amorphous metal particles are heat-treated. On the other hand, when the content ratio f of Ti exceeds the upper limit value, the amorphization is inhibited, and there is a possibility that crystallization is likely to occur when the amorphous metal particles are heat-treated.

[0036] When Co (cobalt) is also added in a trace amount together with Al or Ti, it promotes the reduction of strain in cooperation with Al or Ti when the amorphous metal particles are heat-treated. Therefore, in the soft magnetic powder after heat treatment, it is possible to achieve both high magnetic permeability and low coercive force.

[0037] The Co content g satisfies 0≦g≦0.025, preferably 0.001≦g≦0.020, and more preferably 0.003≦g≦0.015. If the Co content g is below the lower limit, the coercive force may not be sufficiently reduced when the amorphous metal particles are heat-treated. On the other hand, if the Co content g is above the upper limit, the amorphousization may be inhibited, and the amorphous metal particles may be easily crystallized when they are heat-treated.

[0038] Moreover, by optimizing the amount ratio of Al and Ti, it is possible to particularly promote the reduction of distortion during heat treatment.

[0039] Specifically, e and f in the composition formula preferably satisfy 0.20≦e / f≦2.50, more preferably 0.40≦e / f≦2.00, and even more preferably 0.60≦e / f≦1.50. When e / f is within the above range, the quantitative balance of Al and Ti is optimized, and the amorphous metal particles can be particularly improved in magnetic permeability and coercivity by heat treatment.

[0040] Furthermore, by optimizing the amount ratio of Al and Co, it is possible to particularly promote the reduction of distortion during heat treatment.

[0041] Specifically, e and g in the composition formula preferably satisfy 0.10≦e / g≦3.00, more preferably 0.20≦e / g≦2.00, and even more preferably 0.30≦e / f≦1.00. When e / g is within the above range, the quantitative balance of Al and Co is optimized, and the amorphous metal particles can be particularly improved in magnetic permeability and coercivity by heat treatment.

[0042] The amorphous metal particles according to the embodiment have the above-mentioned composition formula Fe 100-a-b-c-d-e-f-g Cr a S b B c C d Al e Ti f Cog In addition to the composition represented by the formula (1), impurities may be included. The impurities may include any elements other than those mentioned above, but it is preferable that the total content of the impurities is 0.50 atomic % or less. Within this range, the impurities are unlikely to impair the effects of the present invention.

[0043] The content of each of the impurity elements is preferably 0.05 atomic % or less. Within this range, the impurities are not likely to impair the effects of the present invention, and therefore their inclusion is permitted.

[0044] The composition of the amorphous metal particles according to the embodiment has been described above, but the composition and impurities are identified by the following analytical method.

[0045] Examples of analytical methods include iron and steel-atomic absorption spectrometry specified in JIS G 1257:2000, iron and steel-inductively coupled plasma atomic emission spectrometry specified in JIS G 1258:2007, iron and steel-spark discharge atomic emission spectrometry specified in JIS G 1253:2002, iron and steel-fluorescent X-ray analysis specified in JIS G 1256:1997, and gravimetry, titration, and absorptiometry specified in JIS G 1211 to G 1237.

[0046] Specific examples include a solid-state optical emission spectrometer manufactured by SPECTRO, in particular a spark discharge optical emission spectrometer, model: SPECTROLAB, type: LAVMB08A, and an ICP device, CIROS120 type manufactured by Rigaku Corporation.

[0047] In particular, when identifying C (carbon) and S (sulfur), the oxygen flow combustion (high-frequency induction heating furnace combustion)-infrared absorption method specified in JIS G 1211:2011 is also used. Specifically, the LECO carbon / sulfur analyzer, CS-200, can be used.

[0048] In particular, when specifying N (nitrogen) and O (oxygen), the nitrogen determination method for iron and steel specified in JIS G 1228:1997 and the general method for oxygen determination for metallic materials specified in JIS Z 2613:2006 are also used. Specifically, the LECO oxygen / nitrogen analyzer, TC-300 / EF-300, can be mentioned.

[0049] The surface of the soft magnetic powder may be provided with an insulating coating, if necessary. Examples of the insulating coating include glass, ceramic, and resin materials.

[0050] 1.2.Powder characteristics The average particle size D50 of the soft magnetic powder according to the embodiment is not particularly limited, but is preferably 1 μm or more and 50 μm or less, more preferably 3 μm or more and 30 μm or less, and even more preferably 5 μm or more and 20 μm or less. By using a soft magnetic powder with such an average particle size, the path through which eddy current flows can be shortened. As a result, a soft magnetic powder capable of sufficiently suppressing eddy current loss generated within the particle is obtained.

[0051] If the average particle size of the soft magnetic powder is below the lower limit, the soft magnetic powder becomes too fine, which may reduce the packing property of the soft magnetic powder. This may reduce the compaction density of the powder core, which is an example of a powder compact, and may reduce the magnetic permeability and magnetic flux density of the powder core. On the other hand, if the average particle size of the soft magnetic powder is above the upper limit, the eddy current loss generated within the particles may not be sufficiently suppressed, and the core loss of the powder core may increase.

[0052] The average particle size D50 of the soft magnetic powder is determined as the particle size at which the cumulative 50% from the small diameter side is reached in a volume-based particle size distribution obtained by a laser diffraction method.

[0053] In the volume-based particle size distribution of the soft magnetic powder according to the embodiment, the particle size at 10% cumulative from the small diameter side is defined as D10, and the particle size at 90% cumulative from the small diameter side is defined as D90. In this case, (D90-D10) / D50 is preferably 1.0 to 1.5, more preferably 1.0 to 1.3. (D90-D10) / D50 is an index showing the degree of spread of the particle size distribution, and by having this index within the above range, the filling property of the soft magnetic powder is improved. Therefore, a green compact having particularly high magnetic properties such as magnetic permeability and magnetic flux density can be obtained.

[0054] 1.3.Physical Properties The coercive force of the soft magnetic powder according to the embodiment is not particularly limited, but is preferably 3.0 [Oe] or less (239 [A / m] or less), and more preferably 0.1 [Oe] or more and 2.0 [Oe] or less (8.0 [A / m] or more and 159 [A / m] or less). By using a soft magnetic powder having such a small coercive force, it is possible to manufacture a green compact that can sufficiently suppress hysteresis loss even when used in a high frequency range.

[0055] The coercive force of the soft magnetic powder can be measured, for example, by a vibrating sample magnetometer such as TM-VSM1230-MHHL manufactured by Tamagawa Seisakusho Co., Ltd.

[0056] The soft magnetic powder according to the embodiment preferably has a magnetic permeability, when compressed, of 15 or more at a measurement frequency of 100 kHz, and more preferably 17 or more. Such a soft magnetic powder contributes to the realization of a powder core having excellent magnetic properties.

[0057] The magnetic permeability of the green compact is, for example, the relative magnetic permeability obtained by forming the green compact into a toroidal shape and calculating the self-inductance of the closed magnetic circuit core coil, that is, the effective magnetic permeability. The magnetic permeability is measured using an impedance analyzer at a measurement frequency of 100 kHz. The number of turns of the winding is 7, and the wire diameter of the winding is 0.6 mm.

[0058] 2. Manufacturing method of soft magnetic powder Next, an example of a method for producing the above-mentioned soft magnetic powder will be described.

[0059] The amorphous metal particles may be powders produced by any method. Examples of the production method include various atomization methods such as water atomization, gas atomization, and rotary water flow atomization, as well as pulverization. Among these, particles produced by the atomization method are preferably used for the amorphous metal particles. According to the atomization method, fine powders with good particle shapes can be efficiently produced. Therefore, soft magnetic powders with particularly high packing properties can be obtained.

[0060] Atomization is a method for producing metal powder by colliding molten metal with a liquid or gas jetted at high speed to finely pulverize the molten metal and cool it.

[0061] Of these, the water atomization method uses a liquid such as water as a coolant, sprays it in an inverted cone shape that converges to one point, and causes molten metal to flow down toward this convergence point and collide with it, thereby producing metal powder from molten metal.

[0062] In addition, the rotary water jet atomization method is a method for producing metal powder by supplying a cooling liquid along the inner surface of a cooling cylinder and rotating it along the inner surface while spraying a liquid or gas jet onto molten metal and incorporating the scattered molten metal into the cooling liquid.

[0063] The cooling rate for cooling molten metal in the atomization method is 1×10 4 °C / s or more, and preferably 1×10 5 It is more preferable that the cooling rate is ℃ / s or more. Such rapid cooling preserves the atomic arrangement in the molten metal state until solidification, resulting in amorphous metal particles with a particularly high degree of amorphization and suppressing the variation in composition ratio between the amorphous metal particles. As a result, a homogeneous soft magnetic powder is obtained.

[0064] By subjecting the amorphous metal particles produced by the method described above to a heat treatment, it is possible to improve the magnetic properties and further reduce the coercive force.

[0065] When the crystallization temperature of the amorphous metal particles is Tx, the heating temperature in the heat treatment is preferably Tx-100° C. or more and less than Tx, and more preferably Tx-50° C. or more and less than Tx.

[0066] When the heating temperature is within the above range, the heating time in the heat treatment is preferably from 5 minutes to 120 minutes, and more preferably from 5 minutes to 60 minutes.

[0067] By carrying out the heat treatment under such heating conditions, it is possible to alleviate the residual stress caused by the rapid solidification during the production of the amorphous metal particles, thereby alleviating the distortion in the amorphous metal particles, thereby reducing the coercive force and improving the magnetic properties.

[0068] The produced soft magnetic powder may be classified as necessary. Examples of the classification method include dry classification such as sieving classification, inertial classification, and centrifugal classification, and wet classification such as sedimentation classification.

[0069] 3. Powder cores and magnetic components Next, the powder magnetic core and the magnetic element according to the embodiment will be described.

[0070] The magnetic element according to the embodiment can be applied to various magnetic elements having a magnetic core, such as a choke coil, an inductor, a noise filter, a reactor, a transformer, a motor, an actuator, an electromagnetic valve, a generator, etc. Furthermore, the powder magnetic core according to the embodiment can be applied to the magnetic cores included in these magnetic elements.

[0071] Two types of coil components will be described below as representative examples of the magnetic element. 3.1.Toroidal type First, a toroidal type coil component, which is an example of a magnetic element according to the embodiment, will be described. FIG. 1 is a plan view that illustrates a schematic diagram of a toroidal type coil component.

[0072] 1 has a ring-shaped powder core 11 and a conductive wire 12 wound around this powder core 11. Such a coil component 10 is generally called a toroidal coil.

[0073] The powder magnetic core 11 is obtained by mixing the soft magnetic powder according to the embodiment with a binder, supplying the mixture to a molding die, and pressing and molding it. That is, the powder magnetic core 11 is a compact containing the soft magnetic powder according to the embodiment. In such a powder magnetic core 11, the soft magnetic powder has a low coercive force and a high magnetic permeability. Therefore, the coil component 10 including the powder magnetic core 11 has a low core loss in the high frequency range and high magnetic properties such as magnetic permeability and magnetic flux density. Therefore, when the coil component 10 is mounted on an electronic device or the like, it is possible to reduce the power consumption of the electronic device or the like and to achieve high performance and miniaturization.

[0074] Examples of the binder used to manufacture the powder magnetic core 11 include organic materials such as silicone resins, epoxy resins, phenol resins, polyamide resins, polyimide resins, and polyphenylene sulfide resins, inorganic materials such as phosphates such as magnesium phosphate, calcium phosphate, zinc phosphate, manganese phosphate, and cadmium phosphate, and silicates such as sodium silicate, and thermosetting polyimide or epoxy resins are particularly preferred. These resin materials are easily cured by heating and have excellent heat resistance. Therefore, the ease of manufacture and heat resistance of the powder magnetic core 11 can be improved. The binder may be added as necessary, or may be omitted.

[0075] The ratio of binder to soft magnetic powder varies slightly depending on the desired magnetic properties, mechanical properties, allowable eddy current loss, etc. of the powder core 11 to be produced, but is preferably about 0.5% by mass to 5% by mass, and more preferably about 1% by mass to 3% by mass. This allows the particles of the soft magnetic powder to be sufficiently bound together, while providing a coil component 10 with excellent magnetic properties. If necessary, various additives may be added to the mixture for any purpose.

[0076] The conductive wire 12 may be made of a highly conductive material, such as a metal material containing Cu, Al, Ag, Au, Ni, etc. An insulating film may be provided on the surface of the conductive wire 12 as necessary.

[0077] The shape of the powder magnetic core 11 is not limited to the ring shape shown in FIG. 1, but may be, for example, a ring shape in which part of the ring is missing, a shape in which the longitudinal direction is linear, or a sheet or film shape.

[0078] Furthermore, the dust core 11 may contain soft magnetic powder other than the soft magnetic powder according to the embodiment described above or non-magnetic powder, as necessary.

[0079] As described above, the coil component 10, which is a magnetic element, includes the dust core 11 containing the soft magnetic powder described above. This makes it possible to realize the coil component 10 with low core loss and excellent magnetic properties.

[0080] 3.2.Closed magnetic circuit type Next, a closed magnetic circuit type coil component, which is an example of a magnetic element according to the embodiment, will be described. FIG. 2 is a see-through perspective view that typically shows a closed magnetic circuit type coil component.

[0081] The closed magnetic circuit type coil component will be described below, but in the following description, the differences from the toroidal type coil component will be mainly described, and a description of similar points will be omitted.

[0082] 2, the coil component 20 according to this embodiment is formed by embedding a conductor wire 22 formed into a coil shape inside a powder core 21. That is, the coil component 20, which is a magnetic element, includes a powder core 21 containing the soft magnetic powder described above, and is formed by molding the conductor wire 22 with the powder core 21. This powder core 21 has a similar configuration to the powder core 11 described above. This makes it possible to realize a coil component 20 with low core loss and excellent magnetic properties.

[0083] The coil component 20 of this type can be easily obtained as a relatively small one. Moreover, the coil component 20 has high magnetic properties and low core loss. Therefore, when the coil component 20 is mounted in an electronic device or the like, it is possible to reduce the power consumption of the electronic device or the like and to achieve high performance and miniaturization.

[0084] Furthermore, because the conductive wire 22 is embedded inside the powder core 21, a gap is unlikely to occur between the conductive wire 22 and the powder core 21. This makes it possible to suppress vibrations caused by magnetostriction of the powder core 21, and also to suppress the generation of noise associated with this vibration.

[0085] The shape of the powder magnetic core 21 is not limited to the shape shown in FIG. 2, and may be a sheet, a film, or the like.

[0086] Furthermore, the dust core 21 may contain soft magnetic powder other than the soft magnetic powder according to the embodiment described above or non-magnetic powder, as necessary.

[0087] 4.Electronic equipment Next, an electronic device including the magnetic element according to the embodiment will be described with reference to FIGS.

[0088] Fig. 3 is a perspective view showing a mobile personal computer, which is an electronic device including a magnetic element according to the embodiment. The personal computer 1100 shown in Fig. 3 includes a main body 1104 including a keyboard 1102, and a display unit 1106 including a display unit 100. The display unit 1106 is rotatably supported by the main body 1104 via a hinge structure. Such a personal computer 1100 includes a magnetic element 1000, such as a choke coil or inductor for a switching power supply, or a motor.

[0089] Fig. 4 is a plan view showing a smartphone, which is an electronic device including the magnetic element according to the embodiment. The smartphone 1200 shown in Fig. 4 includes a plurality of operation buttons 1202, an earpiece 1204, and a mouthpiece 1206. A display unit 100 is disposed between the operation buttons 1202 and the earpiece 1204. Such a smartphone 1200 includes a magnetic element 1000, such as an inductor, a noise filter, or a motor.

[0090] 5 is a perspective view showing a digital still camera, which is an electronic device including the magnetic element according to the embodiment. The digital still camera 1300 photoelectrically converts an optical image of a subject using an imaging element such as a CCD (Charge Coupled Device) to generate an imaging signal.

[0091] 5 includes a display unit 100 provided on the back of a case 1302. The display unit 100 functions as a viewfinder that displays a subject as an electronic image. In addition, a light receiving unit 1304 including an optical lens, a CCD, etc. is provided on the front side of the case 1302, i.e., on the back side in the figure.

[0092] When the photographer checks the subject image displayed on the display unit 100 and presses the shutter button 1306, the image signal of the CCD at that time is transferred to and stored in memory 1308. Such a digital still camera 1300 also has a built-in magnetic element 1000, such as an inductor or a noise filter.

[0093] Examples of electronic devices according to the embodiments include the personal computer of FIG. 3, the smartphone of FIG. 4, and the digital still camera of FIG. 5, as well as mobile phones, tablet terminals, watches, inkjet discharge devices such as inkjet printers, laptop personal computers, televisions, video cameras, video tape recorders, car navigation devices, pagers, electronic organizers, electronic dictionaries, calculators, electronic game devices, word processors, workstations, videophones, security television monitors, electronic binoculars, POS terminals, medical devices such as electronic thermometers, blood pressure monitors, blood glucose meters, electrocardiogram measuring devices, ultrasonic diagnostic devices, and electronic endoscopes, fish finders, various measuring devices, instruments for vehicles, aircraft, and ships, mobile object control devices such as automobile control devices, aircraft control devices, railway vehicle control devices, and ship control devices, and flight simulators.

[0094] As described above, such electronic devices include the magnetic element according to the embodiment, thereby making it possible to enjoy the effects of the magnetic element, such as low coercivity and high magnetic permeability, and to improve the performance of the electronic devices.

[0095] 5. Mobile Next, a moving body including the magnetic element according to this embodiment will be described with reference to FIG. FIG. 6 is a perspective view showing an automobile, which is a moving object including the magnetic element according to the embodiment.

[0096] The magnetic element 1000 is built into the automobile 1500. Specifically, the magnetic element 1000 is built into various automobile parts, such as a car navigation system, an antilock braking system (ABS), an engine control unit, a battery control unit for a hybrid automobile or an electric automobile, a vehicle attitude control system, an electronic control unit (ECU) for an automatic driving system, a drive motor, a generator, an air conditioning unit, and the like.

[0097] As described above, such a moving body includes the magnetic element according to the embodiment, thereby making it possible to enjoy the effects of the magnetic element, such as low coercive force and high magnetic permeability, and to improve the performance of the moving body.

[0098] Note that the moving body according to this embodiment may be, for example, a motorcycle, a bicycle, an airplane, a helicopter, a drone, a ship, a submarine, a train, a rocket, a spaceship, or the like, in addition to the automobile shown in FIG.

[0099] The soft magnetic powder, dust core, magnetic element, electronic device, and mobile object of the present invention have been described above based on the preferred embodiments, but the present invention is not limited thereto.

[0100] For example, in the above embodiment, a powder compact such as a powder core has been described as an example of an application of the soft magnetic powder of the present invention, but the application examples are not limited to this and may also be magnetic devices such as magnetic fluids, magnetic heads, and magnetic shielding sheets.

[0101] Furthermore, the shapes of the dust core and the magnetic element are not limited to those shown in the drawings, and may be any shape. EXAMPLES

[0102] Next, specific examples of the present invention will be described. 6. Manufacturing of soft magnetic powder 6.1. Sample No. 1 First, the raw materials were melted in a high-frequency induction furnace and pulverized by water atomization to obtain amorphous metal particles, which were then classified using a sieve.

[0103] Next, the classified amorphous metal particles were subjected to a heat treatment at 300° C. for 30 minutes in a nitrogen atmosphere to obtain soft magnetic powder of sample No. 1.

[0104] The composition of the obtained amorphous metal particles is shown in Table 1. The composition was determined using a SPECTRO solid-state optical emission spectrometer (spark optical emission spectrometer), model: SPECTROLAB, type: LAVMB08A. The quantitative analysis of C (carbon) was performed using a LECO carbon-sulfur analyzer, CS-200.

[0105] 6.2. Samples No. 2 to 21 A soft magnetic powder was obtained in the same manner as in Sample No. 1, except that the composition of the amorphous metal particles was as shown in Table 1 or Table 2.

[0106] In Tables 1 and 2, among the soft magnetic powders of each sample number, those that correspond to the present invention are indicated as "Examples", and those that do not correspond to the present invention are indicated as "Comparative Examples".

[0107] 7. Evaluation of soft magnetic powder 7.1. Particle size distribution The soft magnetic powder of each sample No. was subjected to particle size distribution measurement. This measurement was performed using a laser diffraction type particle size distribution measuring device, Microtrac, HRA9320-X100, manufactured by Nikkiso Co., Ltd. Then, the particle sizes D10, D50, D90, and (D90-D10) / D50 of the soft magnetic powder were calculated from the particle size distribution. The calculation results are shown in Table 1 or Table 2.

[0108] 7.2.Coercive force The coercive force of the soft magnetic powder of each sample No. was measured using a magnetization measuring device, VSM System TM-VSM1230-MHHL, manufactured by Tamagawa Seisakusho Co., Ltd. The measurement results are shown in Table 1 or Table 2.

[0109] 8. Manufacturing of dust cores and magnetic components Using the soft magnetic powder of each sample number, a dust core and a magnetic element were manufactured as follows.

[0110] First, the soft magnetic powder, the epoxy resin (binder), and the methyl ethyl ketone (organic solvent) were mixed to obtain a mixture. The amount of the epoxy resin added was 2 parts by mass with respect to 100 parts by mass of the soft magnetic powder.

[0111] Next, the obtained mixture was stirred and then dried by heating at a temperature of 150° C. for 30 minutes to obtain a lump-shaped dried body, which was then sieved through a sieve with an opening of 500 μm and pulverized to obtain a granulated powder.

[0112] Next, the obtained granulated powder was filled into a molding die, and a molded body was obtained based on the following molding conditions.

[0113] Molding method: Press molding Shape of molded body: Ring-shaped - Dimensions of molded body: outer diameter φ14mm, inner diameter φ7mm, thickness 3mm Molding pressure: Molding pressure 294MPa

[0114] Next, the binder in the compact was hardened by heating, thereby obtaining a powder magnetic core (toroidal core).

[0115] Next, using the obtained dust core, a magnetic element shown in FIG. 1 was produced based on the following production conditions.

[0116] Conductor material: Cu Conductor diameter: 0.6mm Number of turns (when measuring magnetic permeability): 7 turns Number of turns (when measuring core loss): 36 turns on the primary side, 36 turns on the secondary side

[0117] 9. Evaluation of magnetic elements 9.1.Magnetic permeability The magnetic permeability at a frequency of 100 kHz was measured for the magnetic elements manufactured using the soft magnetic powder of each sample number using an Agilent 4294A precision impedance analyzer. The obtained magnetic permeability was then evaluated against the following evaluation criteria.

[0118] A: Magnetic permeability is 20 or more B: Permeability is 17 or more and less than 20 C: Permeability is 14 or more and less than 17 D: Permeability is less than 14 The evaluation results are shown in Table 1 or Table 2.

[0119] 9.2. Core loss The core loss Pcv was measured for the magnetic elements manufactured using the soft magnetic powder of each sample No. The measurement conditions were a measurement frequency of 1 MHz and a maximum magnetic flux density Bm of 50 mT. The obtained core loss was evaluated according to the following evaluation criteria.

[0120] A: Very low core loss (200kW / m in Table 1) 3 Less than 400kW / m in Table 2 3 less than) B: Slightly lower core loss (200kW / m in Table 1) 3 More than 250kW / m 3 Less than 400kW / m in Table 2 3 More than 500kW / m 3 less than) C: Core loss is somewhat high (250kW / m in Table 1) 3 More than 300kW / m 3 Less than 500kW / m in Table 2 3 More than 600kW / m 3 less than) D: Very high core loss (300 kW / m in Table 1) 3 In Table 2, the above is 600kW / m 3 End) The evaluation results are shown in Table 1 or Table 2.

[0121] [Table 1]

[0122] [Table 2]

[0123] As is clear from Tables 1 and 2, the soft magnetic powders of the Examples had lower coercive force than the soft magnetic powders of the Comparative Examples. Furthermore, the magnetic elements using the soft magnetic powders of the Examples also had good magnetic permeability and core loss.

[0124] In addition, when the soft magnetic powders of the examples and comparative examples were not subjected to heat treatment, the coercive force was 8.0 [Oe] or more. Therefore, it was revealed that the present invention can realize a soft magnetic powder that can sufficiently reduce the coercive force by heat treatment and can realize high magnetic permeability. [Explanation of symbols]

[0125] 10...coil part, 11...powder magnetic core, 12...conductor, 20...coil part, 21...powder magnetic core, 22...conductor, 100...display part, 1000...magnetic element, 1100...personal computer, 1102...keyboard, 1104...main body, 1106...display unit, 1200...smartphone, 1202...operation button, 1204...earpiece, 1206...mouthpiece, 1300...digital still camera, 1302...case, 1304...light receiving unit, 1306...shutter button, 1308...memory, 1500...automobile

Claims

1. Composition formula:Fe 100-a-b-c-d-e-f-g Cr a Si b B c C d A e Ti f Coco g [wherein a, b, c, d, e, f and g are numbers representing atomic percentages, 0<a≦3.0, 5.0≦b≦15.0, 7.0≦c≦15.0, 0.1≦d≦3.0, 0<e≦0.016, 0<f≦0.009, 0≦g≦0.025, Satisfy. ] A soft magnetic powder comprising amorphous metal particles having a composition represented by the formula:

2. 2. The soft magnetic powder according to claim 1, wherein e and f in the composition formula satisfy 0.20≦e / f≦2.

50.

3. 3. The soft magnetic powder according to claim 1, wherein e and g in the composition formula satisfy 0.10≦e / g≦3.

00.

4. A dust core comprising the soft magnetic powder according to claim 1 .

5. A magnetic element comprising the powder magnetic core according to claim 4.

6. An electronic device comprising the magnetic element according to claim 5 .

7. A moving body comprising the magnetic element according to claim 5 .

Citation Information

Patent Citations

  • Alloy powder and method for producing the same

    JP2010007100A

  • ALLOY COMPOSITION, Fe-BASED NANOCRYSTALLINE ALLOY AND METHOD FOR PRODUCING THE Fe-BASED NANOCRYSTALLINE ALLOY, AND MAGNETIC COMPONENT

    JP2012012699A

  • Soft magnetic alloy, soft magnetic alloy magnetic core, and manufacturing method of soft magnetic alloy

    JP2013118348A

  • Amorphous alloy powder, dust core, magnetic element and electronic apparatus

    JP2014167137A

  • Iron-based metallic glass alloy powder

    JP2014169482A